Analisis Pesan Dakwah Nabi Muhammad SAW Dalam Piagam Madinah - Suparman, Suparman (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2024)
Prophet Muhammad SAW is the most important figure when discussing the da'wah activities that exist in and outside the Arab region until it spread throughout the world as it is today. Based on historical facts, his stories and examples in da'wah contain messages of goodness and wisdom, some examples of his da'wah messages can be seen in the Medina Charter which is used as a written da'wah media, legal and recognized by the Medina community at that time. The purpose of this study is to find the da'wah messages contained in the document. This study uses a descriptive qualitative method. The subject of this study is the text of the Medina Charter and the object is the da'wah message. The data collection technique in this study was carried out by collecting information and data obtained from various literature, such as books, scriptures, and journals. The data analysis technique was carried out using the content analysis method. The results of the study show that the 47 articles of the Medina Charter contain Islamic teachings in the holy book and the prophet's sunnah, including messages of unity of the people, brotherhood, equality, freedom, harmony between religious communities, doing good to neighbors, helping each other, peace, recommendations for deliberation, justice, implementation of the law, leadership, and piety which are proven or accompanied by explanations of each message in the Qur'an and hadith. Thus, it can be concluded that the tendency of the messages contained in the Medina Charter is a message of preaching to realize a social life that is in accordance with the rules of Islamic teachings in the Qur'an and hadith